PERANCANGAN SISTEM PERAMALAN CUACA BERBASIS LOGIKA FUZZY - Ema Sastri Puspita; Liza Yulianti (UNIVED Press, 2016)
This study aims to Implement Sugeno Fuzzy Logic method for weather forecasts and testing the accuracy of this research. The problem definition covers only the Data-Based Design of Weather Forecasting Sugeno Fuzzy Logic method using Matlab so as not to come out of the issues raised, it is used as the input is temperature, humidity and wind. In determining the results of research is an important weather forecasting particularly determined membership functions and the rule is used. Fuzzy logic using Sugeno method is best used in forecasting for the accuracy above 60%. The more variables that are used as input it will produce better output (inaccurate).Keywords: Weather Forecasting, Fuzzy Logic